Home is Where the Lab is: A Comparison of Online and Lab Data From a Time-sensitive Study of Interruption (Human Computation, 2015)
While experiments have been run online for some time with positive results, there are still outstanding questions about the kinds of tasks that can be successfully deployed to remotely situated online participants. Some tasks, such as menu selection, have worked well but these do not represent the gamut of tasks that interest HCI researchers. In particular, we wondered whether long-lasting, time-sensitive tasks that require continuous concentration could work successfully online, given the confounding effects that might accompany the online deployment of such a task. We ran an archetypal interruption experiment both online and in the lab to investigate whether studies demonstrating such characteristics might be more vulnerable to a loss of control than the short, time-insensitive studies that are representative of the majority of previous online studies. Statistical comparisons showed no significant differences in performance on a number of dimensions. However, there were issues with data quality that stemmed from participants misunderstanding the task. Our findings suggest that long-lasting experiments using time-sensitive performance measures can be run online but that care must be taken when introducing participants to experimental procedures.
Keywords: Online experimentation; interruptions; multitasking; human performance